PENGARUH ATRAKSI WISATA, FASILITAS, DAN PROMOSI TERHADAP JUMLAH WISATAWAN DI TAMAN BUNGA CELOSIA - Ufililai Sihura; Julian Andriani Putri (LPSDI Bina Patria, 2025)
This study aims to analyze the influence of tourist attractions, facilities, and promotions on the number of tourists visiting Celosia Flower Park. The selection of this topic is based on the importance of the role of the destination as one of the main attractions in its area, but faces challenges in maintaining the consistency of the number of tourist visits. The method used is quantitative with a survey approach, using a questionnaire as an instrument for data collection. The sample consisted of visitors to Celosia Flower Park, and the data was analyzed using multiple linear regression techniques using SPSS software. The results showed that the three independent variables of tourist attractions, facilities, and promotions had a significant effect both simultaneously and partially on the number of tourist visits. Promotion proved to be the most dominant factor, followed by attractions and facilities. The R Square value of 0.653 indicates that the model can explain 65.3% of the variation in the number of tourists. These results emphasize the importance of an effective promotion strategy, supported by the development of attractions and improvement of facilities, in order to increase the competitiveness of tourist destinations. This study provides an empirical contribution for tourism managers in designing data-based policies to increase visits sustainably.